Failure analysis on Kriss motorcycles handle locking mechanism / Muhammad Ali @ Harun - Ali @ Harun, Muhammad (2003)
Repeat cases of stolen motorcycle has been on the rise for the past few years. One of the main causes attributing to this increase is due to the failure in the locking mechanism. This thesis is about the failure analysis on the kriss motorcycles handle-locking mechanism. The objectives of the study are to identify the types of failure, to determine the required or maximum load that causes a failure, and finally to propose a way to improve the strength of the locking-mechanism. Tensile testing machine is used to determine the load at failure and its mode. The analysis is then continued by using Finite Element Analysis in order to understand the overall distributions of stresses in the locking components so that an improvement can be made accordingly. In the final phase of the project, we provide some suggestion to improve our design of the locking mechanism in order to enhance the safety aspect by providing much needed security to the owners of the motorcycles.